2013
DOI: 10.1089/gtmb.2012.0161
|View full text |Cite
|
Sign up to set email alerts
|

Association of Uridine Diphosphate-Glucuronosyltransferase 2B Gene Variants with Serum Glucuronide Levels and Prostate Cancer Risk

Abstract: Aims: Uridine diphosphate-glucuronosyltransferase 2B (UGT2B) enzymes conjugate testosterone metabolites to enable their excretion in humans. The functional significance of the UGT2B genetic variants has never been described in humans. We evaluated UGT2B variants in relation to plasma androstane-3a,17b-diol-glucuronide (AAG) levels and the prostate cancer risk. Results: AAG levels were measured in sera from 150 controls and compared to the polymorphisms of UGT2B17, UGT2B15, and UGT2B7. Genomic DNA from controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 30 publications
(46 reference statements)
3
19
0
Order By: Relevance
“…PCDH11Y mRNA in normal prostates, primary prostate tumors, and untreated PCa is low but increases significantly in CRPC (29), consistent with a negative correlation between NCOR1 and PCDH11Y observed in LNCaP cells. AR-repressed genes, UGT2B15 and UGT2B17, cause DHT conjugation and excretion (28, 37) and are associated with prostate cancer risk (38, 39). We show that NCOR1 is required for optimal UGT2B15 expression under all conditions, while for UGT2B17 expression of NCOR1 was required only in the presence of androgens.…”
Section: Discussionmentioning
confidence: 99%
“…PCDH11Y mRNA in normal prostates, primary prostate tumors, and untreated PCa is low but increases significantly in CRPC (29), consistent with a negative correlation between NCOR1 and PCDH11Y observed in LNCaP cells. AR-repressed genes, UGT2B15 and UGT2B17, cause DHT conjugation and excretion (28, 37) and are associated with prostate cancer risk (38, 39). We show that NCOR1 is required for optimal UGT2B15 expression under all conditions, while for UGT2B17 expression of NCOR1 was required only in the presence of androgens.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of two studies with different sample sizes revealed contradictory results: no associations between SNP UGT2B15 D85Y and prostate cancer risk were found in a study with a large sample size [9], whereas a study with a smaller sample size found an increased risk of prostate cancer associated with the UGT2B15 D85Y variant in Caucasian subjects [32]. In reference to allele dosage, we previously concluded [33], concordant with previous reports [31,32,39], that homozygous carriers of the dominant UGT2B15 D85Y (G) allele missense polymorphism, (rs1902023), had an almost three-fold higher risk of prostate cancer. Our current results further confirm that associations with UGT2B15 polymorphisms are allele dose-dependent and may also be dependent on race/ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental inhibition of these enzymes significantly improves the proproliferative properties of DHT in prostate cancer cells (14), suggesting that they are major determinants for the androgen response. Accordingly, positive associations were reported between prostate cancer risk and a low-activity UGT2B15 allele or a complete UGT2B17 gene deletion (15)(16)(17)(18)(19). On the other hand, various studies illustrated the negative control that androgens exert on UGT2B15 and UGT2B17 expression in prostate cancer cells (14,20,21).…”
Section: Introductionmentioning
confidence: 99%